Environment cost accounting as a tool in effective economic decision making / Norlaila Abdullah - Abdullah, Norlaila (2002)
The Ministry of Science, Technology and Environment has encouraged all Malaysian companies, domestic and multinationals, to develop, implement and improve the companies environmental accounting system. Also, the government has made a very sound proposal requiring companies to disclose in their annual report information pertaining to economic activities undertaken during a given year and denoting its impact on the environment, their environmental policies and proposed social programs to the community and the public at large. This is a very timely requirement for corporation to extend further their responsibility towards people's health and the environment. Environmental issues must not be ignored or else every entity, juridical or otherwise, will suffer. The mission of this paper is to understand the full spectrum of environmental cost accounting as a tool used by top brass management of an organization in making effective economic decision. This will further dwell on the integration of societal (environmental) costs into business decisions involving capital budgeting, cost allocation, process and product design and product life cycle costing and cost of quality and environmental report in the hope that these accounting techniques would increase the visibility of environmental costs to company managers; thus enabling them to manage these cost effectively for the companies benefits and all other stakeholders. This paper will further demonstrate how accounting information is, or can be, used to support corporate environmental strategy and assess environmental performance.